Cartter family papers
Family correspondence between members of the Cartter and Hanford families, including Judge David Kellogg Cartter, his wife, Nancy Hanford Cartter, and their sons, David K. Cartter, Jr., and William H. Cartter. Includes a political letter from Salmon P. Chase, general correspondence, material relating to David Kellogg Cartter's service as U.S. minister to Bolivia, and papers pertaining to the trial of Charles Guiteau.
Members of the Cartter (Carter) families of Ohio.
Collection material in English.
Keywords: Cartter, David K. -- 1812-1887 -- Correspondence; Cartter, David Kellogg, -- Jr. -- Correspondence; Cartter, Nancy Hanford -- Correspondence; Cartter, William H. -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Guiteau, Charles Julius, -- 1841-1882.; Carter family; Hanford family; Diplomatic and consular service, American -- Bolivia; Bolivia -- Foreign relations -- United States; United States -- Foreign relations -- Bolivia